2011
DOI: 10.1016/j.socscimed.2011.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Household and community HIV/AIDS status and child malnutrition in sub-Saharan Africa: Evidence from the demographic and health surveys

Abstract: This paper examines the extent to which under five children in households or communities adversely affected by HIV/AIDS are disadvantaged, in comparison with other children in less affected households/communities. The study is based on secondary analysis of the Demographic and Health Survey (DHS) data collected during 2003–2008 from 18 countries in sub-Saharan Africa, where the DHS has included HIV test data for adults of reproductive age. We apply multilevel logistic regression models that take into account t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
66
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 19 publications
8
66
0
1
Order By: Relevance
“…La desnutrición al momento del diagnóstico de VIH de los niños fue de 69,3% considerando solo algún parámetro del diagnóstico nutricional, siendo esto alto y corresponde al déficit nutricional del peso para la edad con el 66,7%, valores parecidos lo hallamos en países en vías de desarrollo como el nuestro [9][10][11] ; esto representa el riesgo de 10,5 veces más de tener un déficit del peso para la edad en niños con VIH en comparación con los niños hospitalizados no infectados con VIH, lo que conllevaría a la larga la disminución de la supervivencia según otros estudios 12,13 . Por lo que podemos decir que la pérdida de peso para la edad es uno de los parámetros antropométricos y nutricionales más afectados en los pacientes con VIH, por lo que sugerimos que el personal de salud especialmente las enfermeras deben valorar y conocer este indicador antropométrico de forma periódica con objetivos espe- cíficos en la atención de los niños como parte de evaluación integral de estos pacientes.…”
Section: Discussionunclassified
“…La desnutrición al momento del diagnóstico de VIH de los niños fue de 69,3% considerando solo algún parámetro del diagnóstico nutricional, siendo esto alto y corresponde al déficit nutricional del peso para la edad con el 66,7%, valores parecidos lo hallamos en países en vías de desarrollo como el nuestro [9][10][11] ; esto representa el riesgo de 10,5 veces más de tener un déficit del peso para la edad en niños con VIH en comparación con los niños hospitalizados no infectados con VIH, lo que conllevaría a la larga la disminución de la supervivencia según otros estudios 12,13 . Por lo que podemos decir que la pérdida de peso para la edad es uno de los parámetros antropométricos y nutricionales más afectados en los pacientes con VIH, por lo que sugerimos que el personal de salud especialmente las enfermeras deben valorar y conocer este indicador antropométrico de forma periódica con objetivos espe- cíficos en la atención de los niños como parte de evaluación integral de estos pacientes.…”
Section: Discussionunclassified
“…Prevalences of HIV infection as high as 51% have been reported among malnourished patients in both hospital 23 and community 24 settings. With a national HIV prevalence of 6.3% for children aged 1.5 -4 years in Botswana, 25 there is a strong possibility that a greater proportion of the children in our study were HIV-infected.…”
Section: Discussionmentioning
confidence: 99%
“…An investigation of the nutritional status of children in areas with high HIV prevalence indicates that even maternal HIV infection is associated with a significantly higher relative risk of 1.28 (1.16–1.42) for stunting, 1.26 (1.02–1.55) for wasting, and 1.2 (1.11–1.43) for underweight in children [39]. …”
Section: Impact Of Infections On Nutritionmentioning
confidence: 99%
“…Besides the immediate effect on the patient, a survey in Kenya found that children in HIV-affected households had a higher rate of stunting compared to children from non-HIV-affected families [44]. A review of 18 countries of sub-Saharan Africa confirmed this finding for the years 2003–2008 [45]. This is one of the tragic aspects of the HIV pandemic: even non-infected children are endangered and often die early.…”
Section: Impact Of Infections On Nutritionmentioning
confidence: 99%